Pengaruh Filtrat Bawang Merah (Allium cepa) Terhadap Kadar Formalin pada Ikan Kembung (Rastrelliger sp): Effect of Shallot (Allium cepa) filtrate on Formalin levels in puffer fish (Rastrelliger sp) - Anglania, Shintya Rara; Hanum, Galuh Ratmana (Universitas Muhammadiyah Sidoarjo, 2019)
Fish contains of protein, vitamins, fats and minerals for the body health. Many manufacturers still use formaline for preservation in fish. Onion can reduce the formaline levels in fish with saponin. This study aims to analyze the efficacy of onion to decrease the formaline levels in mackerel fish. This research is experimental laboratory with several parameters, such as: formalin levels, water content, ash content and bacterial analysis. The samples were used 10%, 20%, 30%, 40% and 50% filtrate for 1, 3 and 5 days soaking. The result of the research showed 50% filtrate for 5 days can reduce formalin level is 0.10 mg/L.Water content with 10% filtrate for 1 day is the best result (12.15%), ash content with 10% filtrate with for 1 day is the best result (0.22%). The best results for bacterial analysis in 1 day with 0 colon. This study used Repeated Measure Anova statistical with variation of onion filtrates obtained p-value=0.000 (p<0.05). The results showed that onion filtrates potentially decreased formaline levels in mackerel fish.